Molecular Genetic Characterization of Terreic Acid Pathway in Aspergillus terreus - Guo, Chun-Jun; Sun, Wei-Wen; Bruno, Kenneth S; Wang, Clay C. C (Organic letters, 2014)
Terreic acid is a natural product derived from 6-methylsalicylic acid (6-MSA). A compact gene cluster for its biosynthesis was characterized. Isolation of the intermediates and shunt products from the mutant strains, combined with bioinformatic analyses, allowed for the proposition of a biosynthetic pathway for terreic acid.